Pengaruh Model Pembelajaran Inside-Outside-Circle (IOC) terhadap Kemampuan Pemecahan Masalah Matematika Siswa SMAN 2 Enrekang - Suarti Djafar; Putriyani S; Hafsyah Hafsyah; Rustiani S; Dian Firdiani (Journal on Education, 2023)
The Inside-Outside-Circle learning model or translated as the Small Circle-Large Circle learning model is a cooperative learning model in which two students in pairs from small and large circles share information. This information exchange can be done by all partners at the same time. Based on the results of the post test, it was found that the results of the mathematical problem solving abilities of class X students of SMA Negeri 2 Kota Enrekang on the subject of statistics for the experimental class that applied the Inside-Outside-Circle learning model obtained an average value of 70.13, with a standard deviation of 9, 13 and the control class that applied the direct learning model obtained an average value of 62.42 with a standard deviation of 10.41. Based on the results of the study it can be concluded that it can be concluded that the mathematical problem solving abilities of students who apply the Inside-Outside-Circle learning model are higher than the mathematical problem solving abilities of students who apply the direct learning model. this means that there is an influence of the Inside-Outside-Circle learning model on students' mathematical problem solving abilities.